UNRAVELLING POWER DYNAMICS: A CRITICAL DISCOURSE ANALYSIS OF VOLODYMYS ZELENSKIY’S ADDRESS TO THE UK PARLIAMENT (Lectio: Journal of Language and Language Teaching, 2025)
This study critically analyzes Volodymyr Zelenskiy's speech to the UK Parliament using NormanFairclough’s 3D model of Critical Discourse Analysis (CDA). It examines how textual, discursive,and social practices are constructed to exercise power and shape perceptions during the Russia?Ukraine conflict. Using a qualitative approach, the findings reveal that Zelenskiy’s strategic useof language significantly influenced audience sentiment, positioning Ukraine as a victim ofaggression and Russia as the aggressor. The study highlights the potent role of language inconstructing political reality and mobilizing international support. In addition, certain linguisticstrategies were constructed, emphasizing similar values with the audience and reshaping thediscourse of the war between Russia and Ukraine. The research concluded that through his speech,President Volodymyr Zelenskiy managed to influence the UK parliament members as the audienceand further shaped the discourse of the war between Russia and Ukraine wherein Russia isportrayed as the culprit assailing the core value of humanity and Ukraine, on the other hand, isdepicted as the victim.
Keywords: Analisa Wacana Krits; Norman Fairclough’s 3D Model; Dinamika Kekuasaan; Pidato